Growth of 6- to 10-years-old children from Viana do Castelo, Portugal - Luis Paulo Rodrigues; Pedro Bezerra; Linda Saraiva (Motricidade, 2007)
In the Estudo Morfofuncional da Criança Vianense 1911 elementary school children were measured throughout a four year period, resulting in 4064 individual observations of 6 to 10 year-old children (2054 girls, 2006 boys). The anthropometric variables (height, weight, skinfolds, muscle girth and bone breadth) were used to create percentile reference tables for the local population, and to study their somatotypes in relation to somatic fitness. The results were compared with other national and international studies. Viana's children averaged similar height, weight, muscular girths and bone breadths when compared with other Portuguese studies, but revealed a different growth rhythm and lower weight than the US children. Their skinfolds were also smaller than the reported values for Portugal and for the US. Throughout the elementary school time span, there was atendency to increases in ectomorphy component for boys, and endomorphy for both genders. In conclusion, Viana’s children growth characteristics appear to indicate a level of somatic fitness that is far from mirroring today’s international concerns regarding this matter.